Genistein‐Calcitriol Mitigates Hyperosmotic Stress‐Induced TonEBP, CFTR Dysfunction, VDR Degradation and Inflammation in Dry Eye Disease - Trailokyanath Panigrahi; Sharon D'Souza; Rohit Shetty; Archana Padmanabhan Nair; Anuprita Ghosh; Everette Jacob Remington Nelson; Arkasubhra Ghosh; Swaminathan Sethu (Wiley, 2021)
Dry eye disease (DED) signs and symptoms are causally associated with increased ocular surface (OS) inflammation. Modulation of key regulators of aberrant OS inflammation is of interest for clinical management. We investigated the status and the potential to harness key endogenous protective factors, such as cystic fibrosis transmembrane conductance regulator (CFTR) and vitamin D receptor (VDR) in hyperosmotic stress‐associated inflammation in patients with DED and in vitro. Conjunctival impression cytology samples from control subjects (n = 11) and patients with DED (n = 15) were used to determine the status of hyperosmotic stress (TonEBP/NFAT5), inflammation (IL‐6, IL‐8, IL‐17A/F, TNFα, MMP9, and MCP1), VDR, and intracellular chloride ion (GLRX5) by quantitative polymerase chain reaction and/or immunofluorescence. Human corneal epithelial cells (HCECs) were used to study the effect of CFTR activator (genistein) and vitamin D (calcitriol) in hyperosmotic stress (HOs)‐induced response in vitro. Western blotting was used to determine the expression of these proteins, along with p‐p38. Significantly, higher expression of inflammatory factors, TonEBP, GLRX5, and reduced VDR were observed in patients with DED and in HOs‐induced HCECs in vitro. Expression of TonEBP positively correlated with expression of inflammatory genes in DED. Increased TonEBP and GLRX5 provides confirmation of osmotic stress and chloride ion imbalance in OS epithelium in DED. These along with reduced VDR suggests dysregulated OS homeostasis in DED. Combination of genistein and calcitriol reduced HOs‐induced TonEBP, inflammatory gene expression, and p‐p38, and abated VDR degradation in HCECs. Henceforth, this combination should be further explored for its relevance in the management of DED.